Police subcultural influences on the transfer of training - Dulin, Linda (International journal of police science & management, 2020)
This research assessed subcultural impacts on police motivation to learn and transfer new knowledge to the field by deploying a novel survey instrument, the Police Learning Environment Inventory (PLEI). Surveys were issued to 119 police officers in the southwest and northeast regions of the U.S. Subsequent statistical analyses, employing Ridge and Lasso regression, revealed that various dimensions of police subculture can impact police motivation to learn and apply new knowledge. However, two such dimensions, Innovation and Bureaucratic, were significant in all the statistical modelling. Innovation displayed a consistent and positive relationship with respondent motivation to learn and transfer training. Conversely, the Bureaucratic dimension was negatively associated with this motivation.